Second Five Year Plan Bombay State Banaskantha District - Planning Commission (Planning Commission)
The Banaskantha District of the State of Bombay is,, as its name denotes, the territory situated on and round about the banks of the river Banas. It is composed of a part of the former Banaskantha Agency and the merged States of Palanpur. Danta, Tharad. Wav, the Deodar and Thara Jagirs and old Agency area of Bhabhar. Deodar and Sihori Thanas and the Sub-Thana of Suigam. Situation and Boundary The district, as at present reconstituted, extends from 23-50’ to 24-40’ north Latitude and 17-15 to 73-2’ east Longitude.
Bombay State